The impact of collaborative and cooperative methods on staff’s knowledge in complaint handling - Tita Hariyanti; Ninik Pujaning Dyah; Sabrina Aulia Rahma; Silvy Rahmah Yanthy; Tjatur Budi Winarko (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
To determine the effect of complaint handling training with collaborative and cooperative methods on increasing and retaining staff’s knowledge. This study was a quasi-experimental with pretest and post-test design. The study was conducted from February to April 2019 at Pandaan Hospital. Respondent of the research were 67 hospital staff who often interacted with patients or patient's family. The Friedman's test showed significant differences in values (<0.05). The Wilcoxon test showed a significant difference between pretest compared to post-test 1 and pretest compared to post-test 2 (sig <0.05), while post-test 1 compared to post-test 2 did not show a significant difference in value (sig> 0.05). Complaint handling training with collaborative and cooperative methods affect staff’s knowledge and their knowledge retention